2020
DOI: 10.1080/19490976.2020.1767464
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis and intestinal microbiota—toward establishing cause and effect

Abstract: The intestinal microbiota may be involved, through metabolic gut-brain interactions, in a variety of neurological conditions. In this addendum, we summarize the findings of our recent study investigating the potentially modulatory influence of the microbiome in a transgenic ALS mouse model, and the possible application to human disease. We found that transgenic mice show evidence of dysbiosis, even at the pre-symptomatic stage, and have a more severe disease course under germfree conditions or after receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…The common experimental approach to study the whole microbiota‐immunity‐CNS axis is currently based on animal models. [ 121–124 ] According to the 3Rs principle (replacement, reduction, and refinement) and taking into account some differences of preclinical models with human physiology (e.g., different microbiota composition), advanced in vitro modeling offers a promising and challenging strategy to reduce the experimental in vivo variability and study the complexity of the axis by analyzing each single microenvironment and biological mediator. [ 125 ] The advent of bioengineering and organ‐on‐a‐chip (OOC) technology in the field of cell culture is providing new technological inputs toward more reliable in vitro tools suitable to model also human immune system‐based mechanisms.…”
Section: Immune Communication From Microbiota To Cns‐resident Cellsmentioning
confidence: 99%
“…The common experimental approach to study the whole microbiota‐immunity‐CNS axis is currently based on animal models. [ 121–124 ] According to the 3Rs principle (replacement, reduction, and refinement) and taking into account some differences of preclinical models with human physiology (e.g., different microbiota composition), advanced in vitro modeling offers a promising and challenging strategy to reduce the experimental in vivo variability and study the complexity of the axis by analyzing each single microenvironment and biological mediator. [ 125 ] The advent of bioengineering and organ‐on‐a‐chip (OOC) technology in the field of cell culture is providing new technological inputs toward more reliable in vitro tools suitable to model also human immune system‐based mechanisms.…”
Section: Immune Communication From Microbiota To Cns‐resident Cellsmentioning
confidence: 99%
“…Recently, Blacher and colleagues confirmed a pre-symptomatic distinct microbiome composition in transgenic SOD1 mice and identified commensals such as, Parabacteroides distasonis and Ruminococcus torques adversely affected the disease whereas Akkermansia muciniphila ameliorated the disease (51). Using a combination of untargeted metabolomic profiling and metagenomics, they found that A. muciniphila increased nicotinamide (NAM) levels in the mice' s cerebrospinal fluid, and NAM supplementation was able to improve the mice survival (43). Furthermore, the authors confirmed a distinct microbiome and metabolite configuration in a small group of ALS patients compared to healthy controls (51).…”
Section: Changes In Gut Microbiome Composition In Neurodegeneration and Alsmentioning
confidence: 98%
“…ALS is a very complex disease in which many conditions such as infections or antibiotic exposure, dysphagia, food replacement, motor dysfunction, and lack of movements, could impact the microbiome structure (43). Distinct microbial profiles have been found in many neurological disorders in which the modulation of microbiota (with fecal microbiota transplantation or probiotics administration) has proven to affect brain activity and disease progression (44)(45)(46).…”
Section: Changes In Gut Microbiome Composition In Neurodegeneration and Alsmentioning
confidence: 99%
“…More recently, Gotkine et al identified dysbiosis in an ALS Sod1 transgenic mouse model and in humans with ALS, and further, Sod1 transgenic mice motor function was improved by the introduction of Akkermansia muciniphila , possibly due to its production of nicotinamide [ 202 ]. Another study on the Sod1 transgenic mouse model also found dysbiosis, epigenetic, and immunological changes prior to the onset of motor deficits [ 203 ].…”
Section: Relationships Between the Early Gut Microbiome And Later mentioning
confidence: 99%